2015
DOI: 10.1097/ccm.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

Radial Artery Applanation Tonometry for Continuous Noninvasive Cardiac Output Measurement

Abstract: Continuous cardiac output measurement using the noninvasive applanation tonometry technology is basically feasible in ICU patients after cardiothoracic surgery. The applanation tonometry technology provides cardiac output values with reasonable accuracy and precision of agreement compared with intermittent pulmonary artery thermodilution measurements in a clinical study setting and is able to reliably track cardiac output changes induced by cardiac output-modifying maneuvers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…The results showed substantial disagreement between BP assessed using radial artery applanation tonometry and invasively measured BP. The findings in this cohort are in contrast to previous studies in general ICU patients which found better agreement between BP readings obtained using automated radial artery applanation tonometry and invasive BP measurements [6, 11, 12]. However, the authors pointed out the fact that BP data were not averaged as aggregation of data can lead to underestimation of measurement differences.…”
Section: Blood Pressure Monitoringcontrasting
confidence: 99%
“…The results showed substantial disagreement between BP assessed using radial artery applanation tonometry and invasively measured BP. The findings in this cohort are in contrast to previous studies in general ICU patients which found better agreement between BP readings obtained using automated radial artery applanation tonometry and invasive BP measurements [6, 11, 12]. However, the authors pointed out the fact that BP data were not averaged as aggregation of data can lead to underestimation of measurement differences.…”
Section: Blood Pressure Monitoringcontrasting
confidence: 99%
“…These are uncalibrated, non-invasive, real-time techniques, which are very easy to perform. Many clinical studies have shown they reliably monitor perfusion pressure and CO in the perioperative period [71][72][73]. A moderate to normal relationship between CO estimations was obtained by this type of device in comparison with PiCCO or thermodilution [74][75][76][77].…”
Section: Volume Clamp and Radial Artery Applanation Tonometrymentioning
confidence: 84%
“…An important drawback to the technology is the extreme sensitivity of the sensor position; therefore, two servo motors automatically and continuously reassess the sensor position. Similar to previous devices, the reconstructed arterial wave enables calculation of different advanced hemodynamic variables, including cardiac output ( 27 ). Several validation studies exist for the different T-line generations, mostly with accuracy comparable to volume clamp devices as demonstrated in the meta-analysis by Kim et al ( 21 ).…”
Section: Contemporary Possibilities Of Continuous Nibp Assessmentmentioning
confidence: 99%